2011
DOI: 10.1111/j.1365-2133.2011.10322.x
|View full text |Cite
|
Sign up to set email alerts
|

Viral oncogenesis and its role in nonmelanoma skin cancer

Abstract: In recent years, the contribution of viruses to cutaneous oncogenesis has steadily gained recognition. The archetype is human herpesvirus 8, which is well established as the causative agent in Kaposi sarcoma. Other viruses believed to play a role in nonmelanoma skin cancer include human papillomavirus and the recently described Merkel cell polyomavirus. We review the mechanisms by which these three viruses interact with the host cell, ultraviolet radiation and immunosuppression to result in carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 169 publications
2
27
0
Order By: Relevance
“…In normal cells, UVR upregulates cellular defense processes leading to p53 activation, cell cycle arrest, apoptosis, or DNA repair. Several βPV types (eg, HPV5, HPV8, HPV38, and HPV49) deregulate these crucial cellular regulatory pathways by targeting multiple transcription factors and/or transcriptional regulators, resulting in infected cells that are highly susceptible to chromosomal instability and malignant transformation by UVR 9, 15, 43. Synergy between βPV and UVR has also been documented in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, UVR upregulates cellular defense processes leading to p53 activation, cell cycle arrest, apoptosis, or DNA repair. Several βPV types (eg, HPV5, HPV8, HPV38, and HPV49) deregulate these crucial cellular regulatory pathways by targeting multiple transcription factors and/or transcriptional regulators, resulting in infected cells that are highly susceptible to chromosomal instability and malignant transformation by UVR 9, 15, 43. Synergy between βPV and UVR has also been documented in animal models.…”
Section: Discussionmentioning
confidence: 99%
“…The role of HPV in cutaneous SCC, as well as BCC, is less clear, although recent studies have found more significant associations 11,13,2428 . Immunosuppressed populations have higher rates of HPV infection, and in the absence of large prospective studies, it is difficult to identify whether the immunosuppression or the viral infection is the etiologic factor 11,13,26,28 . Further clouding the picture is the stronger association between the two in those with a greater sensitivity to UVR 29 .…”
Section: Skin Cancer and Oncogenic Virusesmentioning
confidence: 99%
“…The association between multiple cancers and HPV is well established 13,22,23 . The role of HPV in cutaneous SCC, as well as BCC, is less clear, although recent studies have found more significant associations 11,13,2428 .…”
Section: Skin Cancer and Oncogenic Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…Beta HPV types are suspected to play a role, together with UV radiation, in the development of nonmelanoma skin cancer, the most common cancer among Caucasians (9,13,14). In vitro and in vivo mouse models have revealed that E6 and E7 from certain beta HPV types have the ability, like those from the high-risk alpha HPV types, to deregulate molecular pathways related to cell survival, proliferation, and apoptosis The UVB-irradiated (ϩ) and nonirradiated (Ϫ) hTERT PHKs were processed for the oligonucleotide pulldown assay.…”
Section: Discussionmentioning
confidence: 99%